Dyspareunia is associated with chronic pain in premenopausal women with sickle cell disease. Issue 8 (14th September 2018) - Karafin, Matthew S.; Singh, Meenu; Ceesay, Mamaram; Koduri, Sumana; Zhang, Liyun; Simpson, Pippa; Field, Joshua J.
ABSTRACT: Objectives: Pain is common in women with sickle cell disease (SCD), but the prevalence of dyspareunia in this unique patient population is unknown. In this study, we sought to determine whether chronic pain is associated with an increased prevalence of dyspareunia in premenopausal women with SCD. Methods: A cross-sectional study of premenopausal women with SCD was systematically assessed for symptoms of dyspareunia and chronic pain using a standard questionnaire. These results were correlated with each subject's clinical pain phenotype determined by a review of the patient's electronic medical record. Results: Ninety-one premenopausal women with SCD were examined. Thirty-two percent of the women reported dyspareunia. Women with dyspareunia were more likely to have a history of chronic pain (90% versus 61%, p  = .006), report more pain days per week (median (interquartile range): 6 (4–7) vs. 3 (0–7), p  = .005)), and had a higher oral morphine equivalent dose (145 (45–226) mg vs. 60 (9–160) mg, p  = .030). Using a multivariable classification tree analysis, number of days of pain experienced per week was an important predictor of dyspareunia ( p  = .001). Conclusion: Dyspareunia is common in women with SCD, and more common in women with SCD and chronic pain. Providers should assess women with SCD for dyspareunia, especially those with a chronic pain syndrome.